Strategi BNNK Sleman dalam Mengurangi Penyalahgunaan dan Peredaran Gelap Narkoba: Perspektif Collaborative Governance: BNNK Sleman's Strategy in Reducing Drug Abuse and Illicit Trafficking: Collaborative Governance Perspective - Noviyanti, Marlina (Anterior Jurnal, 2024)
Drug abuse and illicit trafficking remain pressing issues for Indonesia through 2024. This is evident from the increase in drug abuse prevalence in Indonesia by 1.73%, according to a National survey conducted in 2023. The widespread negative impacts make addressing this issue increasingly complex and multidimensional. Sleman has become one of the districts in Yogyakarta that receives special attention in this matter topic. Factors such as student migration, urbanization, and tourism development are the main drivers of the high risk of drug abuse in this area. BNNK Sleman is responsible for designing and implementing effective strategies to reduce and prevent drug abuse and illicit trafficking in the Sleman District. The primary goal of this study is to identify and analyze BNNK Sleman's strategies through the lens of Collaborative Governance. The research method used in this study is a descriptive qualitative approach, with purposive sampling selected as the sampling method. Data were collected through three main methods: direct observation, in-depth interviews, and documentation. The comparison of observational and interview data reveals that the principles of inclusiveness, transparency, accountability, cross-sector collaboration, face-to-face dialogue, and trust-building have been integrated into effective strategies with varying degrees of success. Active community participation, the use of digital technology, and strong accountability are key elements of this strategy. This study highlights the importance of enhancing transparency and accountability through technology to improve public participation and the sustainability of cross-sector collaboration, while also providing significant insights into the implementation of Collaborative Governance at the local level.